Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

For a square matrix $A$. Define $exp(A)=I+\sum_{n}A^{n}/(n!)$ . I need to prove two things

  1. exp(A) converges and is invertible.
  2. Its inverse is given by exp(-A).

Second part is straightforward. Can anyone help on first part?

share|improve this question
    
Can you use Schur decomposition? –  Tunococ Nov 27 '12 at 20:22
    
ok, you mean to prove convergernce with the resulting triangular matrix? –  dineshdileep Nov 28 '12 at 2:39
add comment

1 Answer

up vote 4 down vote accepted

We can show convergence by normal convergence.

$\sum_{k=0}^{\infty} ||\frac{A^k}{k!}|| \le \sum_{k=0}^{\infty} \frac{||A||^k}{k!} = e^{||A||}$. Where $||\cdot||$ is a sub-multiplicative norm (e.g. operator norm)

For invertibility, there's probably a nicer way to show this, but I would just show that if $A$ and $B$ commute, then $e^{A+B} = e^{A}e^{B}$.

$e^{A+B} = \sum_{k=0}^{\infty} \frac{(A+B)^k}{k!} = \sum_{k=0}^{\infty} \sum_{i=0}^k \frac{A^i B^{k-i}}{k!} \binom{k}{i} = \sum_{k=0}^{\infty} \sum_{i=0}^k \frac{A^i B^{k-i}}{i! (k-i)!} = \sum_{k=0}^{\infty} \sum_{i+h=k} \frac{A^i B^{h}}{i! h!} = \sum_{i=0}^{\infty} \sum_{h=0}^{\infty} \frac{A^i B^{h}}{i! h!} = e^A e^B$

$A$ and $-A$ commute so $e^A e^{-A}= e^{A - A} = e^{0} = I$

share|improve this answer
1  
+1 Beat me to it. For convergence work we must assume that the entries of $A$ are either real or complex numbers, but that is not unreasonable. It fails for e.g. $A=I$ in the $p$-adics :-) –  Jyrki Lahtonen Nov 27 '12 at 20:57
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.